2020
DOI: 10.1371/journal.pone.0232880
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic changes in energetic reserves, digestive enzymes, amino acid and energy content of Lithodes santolla (Anomura: Lithodidae): Baseline for culture

Abstract: The southern king crab (SKC) Lithodes santolla is an important commercial species in southern South America. Fishing pressure has caused the deterioration of its stocks. Currently, culture techniques are being developed for producing SKC juveniles to enhance the natural population and to recover the fishing stock. Therefore, it is necessary to know about physiology, energetic and nutritional requirements for SKC maintenance in hatchery. Thus, this study aims to evaluate the biochemical and physiological change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 92 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…Another element that could contribute to suboptimum LH conditions is the natural shift in the conditions for wild RKCs from juvenile to adult. During the ontogenetic stages, from juvenile RKCs, their natural habitat and, thus, food source may change, and that size gain and habitat shift often occur concomitantly [26,30]. In our study, the same habitat and feed (shrimp, herring, sea urchins, and capelin) were used through the entire LH period of 23 months.…”
Section: Discussionmentioning
confidence: 99%
“…Another element that could contribute to suboptimum LH conditions is the natural shift in the conditions for wild RKCs from juvenile to adult. During the ontogenetic stages, from juvenile RKCs, their natural habitat and, thus, food source may change, and that size gain and habitat shift often occur concomitantly [26,30]. In our study, the same habitat and feed (shrimp, herring, sea urchins, and capelin) were used through the entire LH period of 23 months.…”
Section: Discussionmentioning
confidence: 99%
“…A study has shown that the effect of TRP in diets likely depends on the species and developmental stages [ 58 ]. In addition, juvenile crabs have higher amino acid requirements than pre-adults and adult crabs [ 59 ]. Therefore, our results suggest that the proper addition of L-TRP, according to the body size of the animals, may reduce oxidative damage.…”
Section: Discussionmentioning
confidence: 99%